2017
DOI: 10.1186/s13071-017-2291-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety of fluralaner oral solution, a novel systemic antiparasitic treatment for chickens, in laying hens after oral administration via drinking water

Abstract: BackgroundPoultry mites are the most significant pest affecting production systems in the egg-laying industry. Fluralaner is a novel systemic insecticide and acaricide that is effective against poultry mites (Dermanyssus gallinae, Ornithonyssus sylviarum) in chickens after oral administration. This study investigated the safety of oral administration of a 1% solution of fluralaner in drinking water to laying hens at the recommended treatment dose and at multiples of this dose.MethodsOne hundred-twenty healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…Water consumption was not affected by fluralaner administrations (ANCOVA: F (1,13.2) = 0.00, P = 0.9622). This is consistent with the results of Prohaczik et al [ 7 ] where no effect on water consumption was detected up to 5× the recommended dose. Fluralaner administrations had no detectable effect on feed consumption.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Water consumption was not affected by fluralaner administrations (ANCOVA: F (1,13.2) = 0.00, P = 0.9622). This is consistent with the results of Prohaczik et al [ 7 ] where no effect on water consumption was detected up to 5× the recommended dose. Fluralaner administrations had no detectable effect on feed consumption.…”
Section: Resultssupporting
confidence: 93%
“…The recommended treatment dosage of fluralaner oral solution for chicken is two administrations of 0.5 mg/kg body weight, given at 7 days interval. The general safety of such fluralaner treatment has been investigated in laying hen by Prohaczik et al [ 7 ]. The authors have shown that fluralaner is well tolerated in poultry, with a high margin of safety.…”
Section: Introductionmentioning
confidence: 99%
“…Prior evidence that the isoxazolines would be effective against lice was reported in a study of dogs naturally infested with the sucking louse Linognathus setosus . Several prior studies that used isoxazolines in poultry also supported the potential efficacy and safety of an isoxazoline against ectoparasites on birds …”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of action of the isoxazolines is inhibition of chloride channels dependent on glutamate and gamma‐aminobutyric acid (GABA) . Drugs in this class have been used successfully in exotic animals for the treatment of a variety of insect and mite infestations . In poultry, isoxazolines have been well‐tolerated and shown to have a high margin of safety for oral dosing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation